Czego nie powiedzial general Kiszczak : z Janem Widackim rozmawia Wojciech Wroblewski - Widacki, Jan.; Wroblewski, Wojciech, 1957- (Warszawa : Polska Oficyna Wydawnicza BGW, 1992)
A documentation and account of the events which occured under the Minister of Internal Affairs - torture, imprisonment, and persecution of innocent people.
Keywords: Kiszczak, Czeslaw; Widacki, Jan -- Interviews; Internal security -- Poland; Political crimes and offenses -- Poland; Poland -- Politics and government -- 1980-1989.